Pengaruh Desain Lobby terhadap Eksistensi Universitas Matana di Gading Serpong - Natasha Shania Abigail; Rahmania Indrianti (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
Gading Serpong is famous for its area which includes many students in it due to the many university areas around it. Some of them have been recognized by many people as a result of the age of the university. Matana emerged as a university for less than 10 years so that he could be said to be a newcomer. Just like a university must meet the recommended criteria and one of them is a lobby facility. The lobby is the starting point in a university. Many activities can be done in the lobby. In 2018 the Matana University succeeded in building a lobby on the corner of a crossroads. This can cause a significant influence on the existence of universities in the Gading Serpong area. Through this research, it is expected to provide knowledge about the influence of lobbying on the existence of universities in the area. The results of this study indicate that there is indeed a strong and significant relationship with r = 0.685 and t = 6.55, between lobbying matana and its influence on the existence of universities in the Gading Serpong area by 47%.